Characterization and Predictors of Paranoid Ideation in Youths - Sousa, Marina (2015)
Paranoid ideation is a common thought process that constitutes a defense against perceived social threats. The current study aimed at the characterization of paranoid ideation in youths and to explore the possible predictors involved in the development of paranoid ideations. Paranoid ideation, shame, submission, early childhood memories and current depressive, anxious and stress symptomatology were assessed in a sample of 1516 Portuguese youths. Higher frequencies of paranoid ideation were observed, particularly in females and youths from lower socioeconomic status. The main predictors identified relates to submissive behaviors and adverse childhood experiences, and especially to shame feelings. The current study emphasizes that the predictors are similar to findings in adults and clinical populations, and future implications to research and clinical practice aiming at paranoid ideations are discussed, as well as the pertinence of the study of mediating factors that allow a wider understanding of this thought process in younger populations and the prevention of psychopathology in adulthood.